A DevOps framework to shorten delivery time for cloud applications. (1st January 2012) - Hosono, Shigeru
This paper proposes DevOps platforms for cloud applications, integrating both the development and operation environment seamlessly. It consists of the client-side integrated development environment (IDE), and the server-side service portfolio and cloud controller. The IDE has requirement definition, architecture design and application prototyping tools, and it can simulate execution of large-scale applications in developers' PCs. The service portfolio incorporates data from these tools and enables automatic data sharing between them, thereby avoiding setback and redundancy. To deploy the applications in the cloud, the cloud controller utilises the resource structures designed in the IDE and generates virtual machines (VMs) from templates, in which a verified OS and middleware for large-scale data processing are packaged. The behaviour of applications and VMs will be automatically monitored and catalogued as feedbacks for the developers. With these comprehensive approaches, the system integration methods can be streamlined and the acceleration of development can be easily demonstrated.